Cytotoxicity and DNA double-strand breaks in human gingival fibroblasts exposed to eluates of dental composites. Issue 2 (February 2018) - Yang, Yang; Reichl, Franz-Xaver; Shi, Jianwei; He, Xiuli; Hickel, Reinhard; Högg, Christof
Abstract: Objective: Previously, single composite components were used to study cytotoxicity and induction of DNA double-strand breaks (DNA-DSBs) of dental composite resins. In the present study, cytotoxicity and induction of DNA-DSBs in human gingival fibroblasts (HGFs) were investigated with dental composite eluates consisting of multiple components. The eluates were qualified and quantified. Methods: The composites Esthet.X ® HD, Venus ®, X-tra fil ®, CLEARFIL™ AP-X, Admira ® Fusion and QuiXfil ® were polymerized and immersed into Dulbecco's modified Eagle's medium (DMEM) for 72 h. Subsequently, HGFs were incubated with the corresponding composite eluates. The cell viability of HGFs was obtained from an XTT assay. DNA-DSBs were determined using a γ-H2AX assay. The qualification and quantification of eluates were performed by gas chromatography/mass spectrometry (GC/MS). Results: HGFs exposed to the eluates of all investigated composites showed no significant loss of cell viability, compared to negative control. Significant DNA-DSBs induction could be found in HGFs exposed to the eluates of Esthet.X ® HD (0.43 ± 0.05 foci/cell) and Venus ® (0.39 ± 0.04 foci/cell), compared to control (0.22 ± 0.03 foci/cell). A total of 12 substances were detected from the investigated composite eluates. Five of them were methacrylates: tetraethyleneglycol dimethacrylate (TEGDMA), 2-hydroxyethyl methacrylate (HEMA), hydroxypropyl methacrylate (HPMA), ethyleneglycol dimethacrylate (EGDMA) and trimethylolpropane trimethacrylate (TMPTMA). The highest concentration of HEMA (110.5 μM), HPMA (86.08 μM) and TMPTMA (4.50 μM) was detected in the eluates of QuiXfil ® . The highest concentration of TEGDMA was 1080 μM in Venus ® eluates and the highest concentration of EGDMA was 3.18 μM in Esthet.X ® HD eluates. Significance: Significant DNA-DSBs induction can be found in HGFs exposed to the eluates of Esthet.X ® HD and Venus ® . The interactive effects among released (co)monomers and additives may influence the cytotoxicity and induction of DNA-DSBs, compared to exposure with single composite component.